Harmonization of Border Communities between Indonesia and the Democratic Republic of Timor Leste - Binsasi, Heribertus; Seran, Remigius; Nino, Handrianus (Institute Of computer Science (IOCS), 2025)
This study attempts to reveal the reality of community harmonization on the border between the Indonesian people and the Democratic Republic of Timor Leste people who live around the border area, precisely in the Haumeni Ana Village area, Bikomi Nilulat District, North Central Timor Regency, with the Oecusse District. By using a qualitative approach and a cultural study perspective, the researcher revealed the existence of harmonization between the two groups of people with different national foundations which in principle are based on cultural similarities as atoin meto (people who live on dry land), the same language speech, namely uab meto, tribal unity framed in the term bae feto bae mone (brothers and sisters) so that various problems that occur are often resolved with a local wisdom approach, namely maloe mamat (serving betel nut), tok tabua (sitting in dialogue together), menu tiun (customary oath) and natoni (customary ritual). The recommendations produced in this study are that strengthening policies related to problems that occur in society are handed over to traditional leaders and the government becomes social control over the ongoing process